Geographic information system application in business site (bank) selection analysis - Lim, Wan Teang, 1986-, author; Mohamad Nor Said, supervisor; Fakulti Geoinformasi dan Harta Tanah (2010)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2010